Unlocking Total factor productivity of smallholder dairy farmers in Tanzania - Lyatuu, Eliamoni T.R.; Komwihangilo, Daniel M.; Msuta, G.; Kelya, Neema; Okeyo Mwai, Ally; Ojango, Julie M.K.; Gebreyohanes, Gebregziabher (2023)
Tanzania is endowed with a diversity of ecosystems, huge number of cattle farming and available arable land. However, the productivity per cow is still very low due various reasons. This study used data from African Asian Dairy Genetic Gains (AADGG) database collected over a period of 2016 to 2023 in combination with mini survey of cost of production done in twenty-four (24) Local Government Authorities (LGAs) to determines factors that influence total factor productivity in the small-scale dairy farm in selected district in Tanzania. Results show that despite of favorable condition for dairy farming, productivity is still low (40%). The low productivity is exuberated by the high cost of feed and treatment (among other costs) within the area of production. However, with improvements in management the cost will be reduced by almost half (47%), hence an increase in productivity per cow. This paper recommends that proper choices of available resources such as breed type, feeding and disease management regimes could increase productivity per animal. It is also suggested that such interventions should be practiced in combination with modernization and transformation of traditional systems of integrated farming that will enhance use of resources efficiently.